A Meshless Method for TM Scattering from Arbitrary Shaped Radially Inhomogeneous Cylinders - Aslanyurek, Birol; Gurbuz, Tolga U. (ELECTROMAGNETICS ACAD, 2021)
A meshless method for fast solution of the electromagnetic scattering problem related to arbitrary shaped radially inhomogeneous cylinders is proposed. This is an important problem since radially inhomogeneous circular cylinders are common in various engineering applications, and deformations such as notches, grooves, and noncircular holes on such cylinders are required for different purposes. This approach is basically an extension of the previously proposed method, which is based on Fourier series representation of the electric field on boundaries. In the original method, a multilayer cylinder with arbitrary shaped homogeneous layers is considered, and accordingly, the general solution of the cylindrical wave equation in homogeneous medium is used. Here we modify the method by considering the general solution in radially inhomogeneous medium and derive compact expressions for the field.
Keywords: Engineering